The Future of Human Rights in the Digital Age: Indonesian Perspectives and Challenges - Firman Aziz; Nanny Mayasari; Sabhan Sabhan; Zulkifli Zulkifli; Moh. Fatah Yasin (Catuspata, 2022)
Protecting human rights in the digital age remains a significant challenge globally, including in Indonesia. Issues such as lack of regulation, censorship and surveillance, cybercrime, technological inequalities, online hate speech and misinformation, and lack of accountability continue to pose significant threats to the protection and promotion of human rights online. Addressing these challenges requires ongoing efforts to promote and defend human rights online through the development of effective legal frameworks, the strengthening of international human rights norms and standards, and efforts to bridge the digital divide and improve access to information and technologies. This research aims to find out the various challenges that arise in the digital era related to human rights by analyzing and synthesizing information obtained through literature studies. There are several important contexts that concern human rights in the digital era, namely, privacy, freedom of expression, access to information, cybersecurity, online discrimination. Challenges that arise globally and nationally are expected to be resolved by the formation of various regulations related to the digital world.